Performance Evaluation of Cyclic Stability and Capacitance of Manganese Oxide Modified Graphene Oxide Nanocomposite for Potential Supercapacitor Applications. (22nd January 2022) - Kumar, R. Ranjith; Thanigaivel, S.; Dey, Nibedita; Priya, A. K.; Karthick, Alagar; Mohanavel, V.; Kannadhasan, S.; Muhibbullah, M.; Osman, Sameh M.
Abstract : Supercapacitors are a revolutionary type of energy storage device. They must be able to charge and discharge quickly while maintaining a high energy density. A storage material's cyclic stability is a desirable feature. The type of electrode materials employed for the specific study design affects supercapacitor performance. Manganese dioxide has long been regarded as one of the best and most abundant materials in nature, having a potentially high specific capacitance. They also offer a wider potential range, more electroactivity, and are more environmentally friendly. However, because of its decreased volume expansion and low conductivity, it is difficult to use as a capacitor material. As a result, carbon-based porous films and supports can be employed to produce critical composites to overcome the current shortcoming. These nanoparticle-based materials will have improved electrical conductivity and a large surface area. Graphene oxide (GO) has a high surface area, thermal stability, and porosity. As an electrode material, many types of MnO2/carbon-based materials have been widely used in supercapacitors. Their overall performance is influenced by their construction processes, metal ratios, electrolyte medium, and voltage factors. Microwave technology was chosen as a cost-efficient and effective alternative to expensive and laborious techniques for fabricating MnO2/GO composites. The production procedure of a supercapacitor has been explored in this study using MnO2-GO composite materials. Using the electrochemical deposition process, the nanocomposite materials of MnO2-GO are significantly deposited on the stainless steel (SS) substrate material. Galvanostatic charge-discharge techniques and cyclic voltammetry (CV) analytical methods were used to investigate the storage and cycle ability of supercapacitors. The composite MnO2-GO supercapacitor has a higher electrochemical capacitance based on these findings.